2013
DOI: 10.1007/s00216-013-7107-7
|View full text |Cite
|
Sign up to set email alerts
|

Detection of tobacco-related biomarkers in urine samples by surface-enhanced Raman spectroscopy coupled with thin-layer chromatography

Abstract: The nicotine metabolites, cotinine and trans-3'-hydroxycotinine (3HC) are considered as superior biomarkers for identifying tobacco exposure. More importantly, the ratio of 3HC to cotinine is a good indicator to phenotype individuals for cytochrome P450 2A6 activity and to individualize pharmacotherapy for tobacco addiction. In this paper, a simple, robust and novel method based on surface-enhanced Raman spectroscopy coupled with thin-layer chromatography (TLC) was developed to directly quantify the biomarkers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 26 publications
0
25
0
Order By: Relevance
“…The calibration of the spectrometer was checked before data collection. The positions (Raman shift) of the main bands of naphthalene 24 were verified, since the compound has characteristic intense and well-spaced bands in the fingerprint region 500 to 1700 cm −1 . The calibration of the spectral response was performed by the equipment supplier and was checked by measuring the spectrum of a tungsten filament lamp with a National Institute of Standards and Technology traceable spectrum.…”
Section: Raman Spectroscopymentioning
confidence: 91%
See 1 more Smart Citation
“…The calibration of the spectrometer was checked before data collection. The positions (Raman shift) of the main bands of naphthalene 24 were verified, since the compound has characteristic intense and well-spaced bands in the fingerprint region 500 to 1700 cm −1 . The calibration of the spectral response was performed by the equipment supplier and was checked by measuring the spectrum of a tungsten filament lamp with a National Institute of Standards and Technology traceable spectrum.…”
Section: Raman Spectroscopymentioning
confidence: 91%
“…Bispo et al 5 used dispersive RS (830 nm) to identify biomarkers (urea, creatinine, and glucose) in the midstream urine of diabetic and hypertensive patients by principal component analysis (PCA) and a discriminating model, suggesting the possibility of diagnosis of clinical complications associated with diabetes and hypertension (HT) through RS. Using the same type of analysis via PCA, RS was also effective in the detection of antibiotics in urine 23 and other metabolites such as biomarkers of nicotine and cotinine for identification of exposure to tobacco smoke (active or passive), 24 and uric acid as indicative of pre-eclampsia in pregnant women. 25 Therefore, it has been demonstrated that RS could be employed in the direct measurement of the concentration of urea and creatinine in human urine samples for biochemical assay.…”
Section: Introductionmentioning
confidence: 99%
“…The combination of TLC and SERS would be propitious for on-site detection due to its simplicity, rapidity, and sensitivity. For example, it has been used for detection of tobacco-related biomarkers in urine samples [22], identification of alkaloids from the seed extract of Syian rue (Peganum harmala) [23], distinguishing from structural analogues [24], and monitoring of chemical reactions [25].…”
Section: Introductionmentioning
confidence: 99%
“…Although nicotine is the major component in tobacco, it is rarely used as a biomarker due to its short half‐life (1‐2 hours) and rapid absorption from the lungs to the bloodstream and finally to the brain. Nicotine metabolizes in the body to a number of compounds, the main metabolite is cotinine which has a longer half‐life and therefore is a preferred biomarker The Raman spectra of pure nicotine and cotinine obtained using near infrared laser excitation at 785 nm as well as their tentative peak assignments are shown in Figure S2 and Table S1. By comparing the spectra of nicotine, cotinine and oral fluid (Figure A), it can be seen that all of the Raman bands for cotinine and nicotine overlap with Raman bands of oral fluid, which made it difficult to differentiate between them (Figure S3).…”
Section: Resultsmentioning
confidence: 99%